THE ROLE OF ATHEROCALCYNOSIS IN THE DEVELOPMENT OF THROMBOTIC SUBTYPE OF ISCHEMIC STROKE AS A CAUSE OF POSTSTROKE COGNITIVE DISORDERS AND DEMENTIA - Rakhimbaeva Gulnora Sattarovna; Shermuhammedova Feruza Qobiljanovna; Mallayev Fayzullo Sohibjonovich (Scholar Express Journals, 2024)
Large artery atherosclerosis (LAA) stands out as a prevalent subtype within the spectrum of ischemic stroke, emerging as a primary contributor to cerebrovascular diseases. The etiology and risk factors associated with LAA stroke reveal a noteworthy association with cerebral small vessel disease (SVD). Clinical investigations have consistently indicated a positive correlation between LAA stroke and various magnetic resonance imaging (MRI) characteristics indicative of cerebral SVD in individuals experiencing ischemic strokes. Recognizing the intertwined nature of these conditions is crucial, given that the therapeutic approaches employed for LAA stroke necessitate concurrent consideration for patients grappling with cerebral SVD.
Keywords: ischemic stroke; cerebral small vessel disease; large artery atherosclerosis